2023
DOI: 10.37934/cfdl.16.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Computational Fluid Dynamics and Its Application in Sport Science: Bibliometric Analysis of Modelling Thermal Comfort in Sport Hall

Boby Rachmat,
Kristi Agust,
Nur Indri Rahayu
et al.

Abstract: Computational Fluid Dynamics (CFD) has become a very effective tool in modeling and analyzing various complex phenomena, including being an integral part of analyzing thermal comfort phenomena. Therefore, this research was carried out to identify developments in the scientific literature related to research on sports science to carry out initial identification of sports hall thermal comfort modeling using dynamic computing concepts, analyzing trends and research focus in this field through bibliometrics. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Research on how to solve LLDPE issues has been well-documented and well-attracted attention for researchers (see Figure 1 from bibliometric analysis in Scopus database), showing increasing number of research time by time. Bibliometric analysis is one of the excellent methods to understand current research trend, as reported elsewhere [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Research on how to solve LLDPE issues has been well-documented and well-attracted attention for researchers (see Figure 1 from bibliometric analysis in Scopus database), showing increasing number of research time by time. Bibliometric analysis is one of the excellent methods to understand current research trend, as reported elsewhere [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%